Answer:
Step-by-step explanation:
integral(x/(1+x^2)^2)dx
=(1/2)integral(2x/(1+x^2)^2)dx
=(1/2)[-1/(1+x^2)] +c
Let 4 + 3x = u
then 3dx = du
or, <span>1/3∫<span>u√</span>du
</span>
= <span>1/3<span>u^<span>3/2</span></span>/(3/2)
</span>
= <span>2/9∗(4+3x<span>)^<span>3/2
I hope my answer has come to your help. Thank you for posting your question here in Brainly. We hope to answer more of your questions and inquiries soon. Have a nice day ahead!
</span></span></span>
Answer:
Start at -150, then add 3(-5), then add 122.2. -150 + 3(-5) + 122.2 = -45.3.
The answer to your question is the letter G.